Nonmarital Fertility in Serbia: An Under-Researched Phenomenon - Stankovic, Biljana B. (Sociološki pregled, 2019)
In Serbia, as well as throughout Europe, there is a trend of an increase in nonmarital fertility over the last several decades. In 2017, 26% of children were born outside of marriage. The paper presents the basic characteristics of nonmarital fertility, based on official statistics and qualitative research conducted by the author. Conclusions about how many nonmarital births take place within nonmarital unions and how many among single mothers, due to the lack of statistical data, are made indirectly. The results of the analysis indicate the adverse socio-economic status of many mothers and their children born out of marriage. This emphasizes the need for institutional support measures for single parent families. The paper also indicates the need to deepen knowledge and increase the scope and quality of data related to the phenomenon of nonmarital births.
Keywords: Serbia; nonmarital fertility; single-parent families